Perawatan Ibu Post Partum Normal Tentang Perawatan Luka Perineum - Jamila Kasim; Hasifah Hasifah (Lembaga Pengembangan Kinerja Dosen, 2024)
The postpartum period is a very important period because complications often occur, including postpartum infections. One of the factors causing postpartum infections can come from injuries to the birth canal which are good media for the development of germs. This article aims to determine the care of normal postpartum mothers regarding perineal wound care. The methods used in making this literature review are PubMed, Google Scholar, Pequest, Sincedirect and Wiley. The results were published from 2019-2024, Results of normal postpartum maternal care regarding perineal wound care in normal postpartum mothers can be given with boiled binahong leaves, how to care for the vagina with cultural care maintenance or preservation, washing with soap and running water and applying betadine, given jusnalo and boiled red betel leaf water is recommended for postpartum mothers who experience perineal wounds.